Answer:
1
Step-by-step explanation:
x-7=-5x-1
x-(-5x)-7=-1
x+5x-7=-1
6x-7=-1
6x=-1+7
6x=6
x=6/6
x=1
I think D is the correct answer.
Answer:
Step-by-step explanation:
First, we need to write down the equations so we can have a vision of the equations.
3x - 6y = -12
x - 2y = -8
Now we find the simpler equation, and we make it to where one of the variables is on one side.
Let's use the bottom equation.
x = 2y - 8
Now we plug in the equation to the other equation.
3(2y - 8) - 6y = -12
6y - 24 - 6y = -12
-24 = -12
0 = 12
This is a false statement. 0 does not equal 12. That means that the equation has no solutions.